The role of hematopoietic stem cell transplantation for pediatric relapsed or refractory non-hodgkin's lymphoma: Results of the Turkish pediatric bone marrow transplantation study group - Hazar, Volkan; Kesik, Vural; Karasu, Gülsün; Öztürk, Gülyüz; Küpesiz, Alphan; Kılıç Çakı, Suar; Ataş, Erman; Uygun, Vedat; Eker, Nurşah; Erbey, Fatih; Bengoa Yılmaz, Şebnem; Emir, Suna; et al. (Nature Publishing Group, 2016)
[Abstract Not Available]
Keywords: Hematopoietic; Pediatri; Lymphoma